(untitled) (Fiep Bulletin - online, 2011)
Recently, dietary habits and lifestyle have changed in most places of the world. These changes in lifestyle induced an increase in prevalence of overweight and obesity in all age groups. The aims of this work was assess the nutritional status of students that participating in the social project "happy child", developed by Metallurgical W3 in Ponta Grossa, Paraná state. Therefore, the sample was composed by 133 students (90 male and 43 female). To determine the nutritional status were measured height and weight, used for Body Mass index (BMI) calculated. There is a difference between body fat mass in male and female. Thus, we used the BMI suggest by CDC (2000), that show the BMI for child among 2 and 20 years old. The results showed that despite the great concern over the increase of children overweight or obesity, the number of children who are underweight or malnourished, it is also very high (26.7 of male and 14% of female). Percentage of female (62%) who meet their weight within the normal range for their age is higher than for males (53%).